Impacts of reindeer grazing and local topography on plant and lichen communities across the reindeer fence along the Finnish-Norwegian border - Winquist, Emelie (Helsingin yliopisto, 2021)
The heath vegetation in the Jauristunturit study area is highly affected by the reindeer fence that was built in the mid-1950s between Finland and Norway, to prevent summer grazing in the Norwegian side. In the study area, the Finnish and Norwegian pastures are used during different seasons, causing differences in reindeer grazing history, and with time differences in vegetation. Additionally, local topography also impacts the vegetation composition and structure creating variation in local vegetation patterns. My research questions are: How vegetation patterns differ between summer- and winter- grazed areas, and which plant functional groups have the most significant difference? How local topography affects vegetation patterns, and does the effect of topography differ between summer and winter pastures? The data was collected from five 400 m long transects that crossed the fence and had vegetation plots with 10-m intervals. The %-cover and height of each vascular plant, bryophyte, and lichen species were estimated from 0.25 m2 plots. Later, species data was grouped into functional groups and general linear models were used to analyze differences in cover, height, species number, biomass, and leaf-area indices between countries. Topography indices were calculated in GIS for each plot and analyzed with random forest models to find out the most important topography indices explaining vegetation patterns. The vegetation data was collected by four teams, and therefore, the comparability in the collected data between teams was analyzed. Significant vegetation differences were found in the ground layer, with higher cover and biomass of bryophytes on the Finnish side (mean biomass 168.2 vs. 65.2 g m-2). Reindeer lichens were more abundant on the Norwegian side (mean biomass 197.0 vs. 2.9 g m-2) which is visible in aerial and satellite images and in the field. Among vascular plants, evergreen dwarf shrubs had higher biomass and leaf area index on the Finnish side and dwarf birch had higher cover and height on the ...